Kelayakan Usaha Penangkaran Bibit Kelapa Sawit (Elaeis guineensis Jacq) (Studi Kasus Pada CV. Karisma Bangun Tama) - Dwijatenaya, Ida Bagus Made Agung (Jurnal Magrobis, 2010)
The purpose of study to know feasibility effort pendling of seedling oil palm and to know the income. This research conducted from July to September 2009 in C.V Karisma Bangun Tama. The feasibility effort pendling of seedling oil palm at CV.Karisma Bangun Tama can measure with R/C ratio > 2 then the effort hane profit and then we measure with R/C ratio < 2 the effort have loss. With the statement, we can determine because the value in the research using rill value to coast output from the effort pendling and seedling oil palm at CV.Karisma Bangun Tama. The result research indicate the effort pendling and seedling of seedlings oil palm at CV.Krisma Bangun Tama have totally production oil palm seedling while one period cultivation of seedlings (12 mount) is have 110.700 seedlings. The acceptante have Rp.2. 767. 500.000,- and income have Rp. 1. 914.665.000,- so the effort pendling of seedlings oil palm of CV. Karisma Bangun Tama suitable can the operation again, because can we see with the value R/C ratio have the value 3,25. And we can say the effort pendling of seedlings oil palm at CV.Karisma Bangun Tama Company in Bangun Sari Subdistrict, Loa Kulu District, Regency of Kutai Kartanegara can to production again because give a good profit.Keywords :  Feasibility study, Seedling Oil Palm